Mathematics Teaching Anxiety Among Pre-Service Teachers - Villalobos-Morales, Katty Ariani (2025)
This study is framed within a growing line of research that seeks to understand the anxiety faced by future teachers when teaching mathematics. The purpose of this research is to analyze the level of anxiety about teaching mathematics among future Primary Education teachers in Costa Rica. The study design is cross-sectional correlational. The sample consisted of 49 participants enrolled in the Bachelor’s and Licentiate programs in Primary Education at the University of Costa Rica, selected through convenience sampling. An adapted version of the Mathematics Teaching Anxiety Scale was employed for data collection. The study analyzed variables such as the least preferred educational level to teach, age, number of courses enrolled in, and the subject participants would least like to teach. One-way ANOVA and Kruskal-Wallis tests were applied to the variables age and least preferred subject to teach, while t-tests and Mann-Whitney U tests were used for the remaining variables. Results indicated a moderate level of mathematics teaching anxiety and revealed significant differences across several variables. Notably, age and the subject least preferred for teaching showed significant differences in the overall anxiety construct and in three of its dimensions, with large effect sizes. Significant differences were also found in the content knowledge dimension regarding the least preferred educational level to teach, also with a large effect size. Additionally, the number of courses enrolled was significantly associated with the didactic knowledge dimension, showing a medium effect size. These findings suggest the need for further exploration and the development and implementation of intervention strategies to reduce mathematics teaching anxiety.